Cahyono PENERAPAN “LESSON STUDY” DENGAN MODEL PEMBELAJARAN “PROBLEM BASED LEARNING” (PBL) DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Cahyono Cahyo Yono (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2020)
ABSTRACT The purpose of the study was to describe the application of "lesson study" using the learning model "Problem Based Learning" (PBL) on PPKn subjects to improve problem solving skills in students. Type of qualitative research with descriptive analysis method. Learners of class VII A Junior High School in Bandung City as the subject of research. This research data is based on the results of "plan", "do", and "see". Processing data with triangulation techniques. The conclusion of the research results is the implementation of "lesson study" using the learning model "Problem Based Learning" (PBL) which is carried out in accordance with the stages of "lesson study" which is "plan", "do", "see". "Lesson study" contributes to a more mature learning planning process, so that teachers feel better prepared in implementing learning. Effective learning can improve the quality of PPKn learning. The implementation of a well-designed "lesson study" can make teachers more creative and innovative in designing, implementing, and evaluating learning. Keywords: Pancasila and Citizenship Education, Problem Based Learning (PBL), Lesson Study